On the Recursive Sequence x(n+!) = x(n-14) / [1 + x(n-2) x(n-5) x(n-8) x(n-11)] - Dağistan Şimşek; Burak Oğul (MANAS: Journal of Engineering)
In this paper, given solutions fort he following difference equationx(n+!) = x(n-14) / [1 + x(n-2) x(n-5) x(n-8) x(n-11)]where the initial conditions are positive real numbers. The initial conditions of the equation are arbitrary positive real numbers. We investigate periodic behavior of this equation. Also some numerical examples and graphs of solutions are given.